Numerical Analysis on the Performance of Aerodynamic Devices on a Car using CFD - Ramachandran, Lingamoorthy; Ishak, Izuan Amin; Arafat, Mohammad; Zolpakar, Nor Atiqah; Zainal Abidin, Shaiful Fadzil; Harun, Dalila (International Journal of Integrated Engineering, 2024)
Car aerodynamics plays a crucial role in enhancing vehicle performance, efficiency, and stability. This study focuses on evaluating the impact of spoilers and diffusers on drag reduction and downforce generation using ANSYS Fluent CFD software. The k-ε turbulence model is employed for computational efficiency in a steady-state flow simulation for precise mapping of complex geometries. Aerodynamic performance is evaluated at speeds of 70 km/h, 110 km/h, and 150 km/h through aerodynamic forces and flow structure. Results indicate that the diffuser alone achieves the lowest drag coefficient (Cd) of 0.3248, while the spoiler alone yields the highest Cd at 0.4023. The combined use of both devices reduces Cd to 0.3412, a 5.59% improvement over the baseline. Additionally, the combination significantly lowers the lift coefficient (Cl) to -0.3324, enhancing handling and performance. This study concludes that the integrated use of spoilers and diffusers contributes to improved vehicle design for greater efficiency and sustainability.